A Preliminary Study of Racialized Brawn and Brain Framing Effects. Issue 1 (2nd January 2017) - Cranmer, Gregory A.; Bowman, Nicholas D.; Goldman, Zachary W.
Abstract : Extant research has established that racially based brawn and brain frames are common within sports media. Framing theory suggests that these brawn and brain frames should influence audience members' behaviors and attitudes, but little empirical evidence to support this notion exists. This study used a quasi-experimental design (Frame x Athlete Race) to understand how exposure to sports news articles that emphasize the physical or mental attributes of White and Black athletes may result in audiences' subsequent observable behaviors or character judgments toward athletes. Results indicated that frames influenced audiences' behaviors in a simulated environment and attitudes regarding athletes' mental abilities, whereas athlete race influenced audiences' attitudes of athletes' physical abilities. These findings support sports scholars' assertions about framing effects and underscore the potential dangers of current sports media trends.